Non-aqueous electrolyte secondary battery

By combining silicon-containing materials and carbon materials into the negative electrode mixture of lithium-ion secondary batteries, and adding appropriate amounts of carbon nanotubes and cyclic esters, the conductive path cutting of the negative electrode active substance and nonaqueous electrolyte in lithium-ion secondary batteries is solved. The consumption problem has achieved high circulation characteristics and low consumption of nonaqueous electrolytes.

CN115362585BActive Publication Date: 2025-02-25PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202180025370.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-03-31
Filing Date
2021-03-25
Publication Date
2025-02-25
Estimated Expiration
2041-03-25

AI Technical Summary

Technical Problem

Due to the large volume change in the lithium-ion secondary battery, the conductive paths between the negative electrode active material particles are cut off, the circulation characteristics are reduced, and the use of carbon nanotubes increases the consumption of nonaqueous electrolytes.

Method used

A negative electrode mixture is used, which contains an anode active substance that can absorb and store and release lithium ions, including silicon-containing materials and carbon materials, and carbon nanotubes of more than 0.005 mass % and less than 0.05 mass % to the negative electrode mixture. The selected cyclic ester is used as the nonaqueous electrolyte.

Benefits of technology

By suppressing the cut-off of the conductive path between the negative electrode active material particles, high circulation characteristics are ensured, and consumption of nonaqueous electrolyte is reduced, and capacity reduction during charging and discharging is prevented.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115362585B_ABST
    Figure CN115362585B_ABST
Patent Text Reader

Abstract

A non-aqueous electrolyte secondary battery comprises: a positive electrode, a negative electrode and a non-aqueous electrolyte. The negative electrode comprises a negative electrode mixture, and the negative electrode mixture comprises: a negative electrode active material capable of electrochemically storing and releasing lithium ions, and carbon nanotubes. The negative electrode active material comprises: a silicon-containing material and a carbonaceous material. The non-aqueous electrolyte comprises at least one cyclic ester selected from the group consisting of cyclic sulfate esters, cyclic sulfites, and sultones. The content of the carbon nanotubes in the negative electrode mixture is 0.005 mass % or more and 0.05 mass % or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a nonaqueous electrolyte secondary battery. Background Art

[0002] Non-aqueous electrolyte secondary batteries represented by lithium-ion secondary batteries include: a positive electrode, a negative electrode, and a non-aqueous electrolyte. As the non-aqueous electrolyte, a non-aqueous electrolyte solution is mainly used. The negative electrode includes a negative electrode mixture containing a negative electrode active material that can electrochemically absorb and release lithium ions. Among the negative electrode active materials, materials that can electrochemically absorb and release lithium ions are used. As such materials, for example, carbonaceous materials, silicon-containing materials, etc. are used. In addition, carbonaceous materials such as carbon fibers and carbon nanotubes that do not absorb and release lithium ions are sometimes added to the negative electrode mixture.

[0003] Patent Document 1 proposes a scheme for using a composite electrode agent for a lithium ion secondary battery, the composite electrode agent comprising: particles containing an element capable of absorbing and releasing lithium ions; carbon particles capable of absorbing and releasing lithium ions; multilayer carbon tubes; and carbon nanofibers.

[0004] Patent document 2 proposes a scheme for using an electrode manufactured as follows for a lithium-ion battery: an active material, a carbon fiber having a fiber diameter of 50 nm to 300 nm, a carbon fiber having a fiber diameter of 5 nm to 400 nm, carbon black, and a binder are dry-mixed to obtain a mixture, a liquid medium is added to the mixture and kneaded, and the mixture is formed into a sheet shape to manufacture.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2014-146519

[0008] Patent Document 2: Japanese Patent Application Publication No. 2014-160590 Summary of the invention

[0009] Silicon-containing materials have large volume changes accompanying the absorption and release of lithium ions. Therefore, if silicon-containing materials are used as negative electrode active materials, the conductive paths between the negative electrode active material particles are cut off, the negative electrode active material particles become easily isolated, and the cycle characteristics are easily reduced. When using negative electrode active materials containing silicon-containing materials, if carbon nanotubes are combined, it becomes easy to ensure the conductivity between the negative electrode active material particles. On the other hand, by using carbon nanotubes, the surface area of ​​the negative electrode mixture increases, the side reactions increase, and the consumption of non-aqueous electrolyte becomes significant.

[0010] One aspect of the present disclosure relates to a non-aqueous electrolyte secondary battery comprising: a positive electrode, a negative electrode, and a non-aqueous electrolyte.

[0011] The negative electrode comprises a negative electrode mixture, wherein the negative electrode mixture comprises: a negative electrode active material capable of electrochemically storing and releasing lithium ions, and carbon nanotubes.

[0012] The negative electrode active material comprises: silicon-containing material and carbonaceous material,

[0013] The nonaqueous electrolyte includes at least one cyclic ester selected from the group consisting of cyclic sulfate esters, cyclic sulfite esters, and sultones,

[0014] The content of the carbon nanotubes in the negative electrode mixture is 0.005 mass % or more and 0.05 mass % or less.

[0015] The reduction of the nonaqueous electrolyte during repeated charge and discharge of the nonaqueous electrolyte secondary battery can be suppressed. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is a schematic perspective view with a portion of the nonaqueous electrolyte secondary battery according to one embodiment of the present disclosure cut away. DETAILED DESCRIPTION

[0017] In non-aqueous electrolyte secondary batteries, although the silicon-containing material used as the negative electrode active material has a high capacity, the volume change accompanying the storage and release of lithium ions during charging and discharging is large. Therefore, in the negative electrode mixture containing the silicon-containing material, the conductive path between the negative electrode active material particles is cut off, and the negative electrode active material particles become easily isolated. As a result, the cycle characteristics are reduced. If this negative electrode mixture further contains carbon nanotubes, the carbon nanotubes are sandwiched between the negative electrode active material particles, thereby suppressing the cutting of the conductive path and ensuring higher cycle characteristics. However, when the negative electrode mixture contains carbon nanotubes, the surface area of ​​the negative electrode mixture increases, the side reactions increase, and the reduction of the non-aqueous electrolyte after repeated charging and discharging becomes significant.

[0018] For cyclic esters such as ethylene sulfite and propane sultone, even if a non-aqueous electrolyte containing such a cyclic ester is combined with a negative electrode mixture that does not contain carbon nanotubes, it is basically not conducive to suppressing the reduction of the non-aqueous electrolyte after repeated charge and discharge. However, if a non-aqueous electrolyte containing such a cyclic ester is combined with a negative electrode mixture containing a specific amount of carbon nanotubes, it is unexpectedly found that the reduction of the non-aqueous electrolyte after repeated charge and discharge is suppressed.

[0019] In view of the above, the non-aqueous electrolyte secondary battery disclosed in the present invention comprises: a positive electrode, a negative electrode and a non-aqueous electrolyte. The negative electrode comprises a negative electrode mixture, and the negative electrode mixture comprises: a negative electrode active material that can electrochemically absorb and release lithium ions, and carbon nanotubes. The negative electrode active material comprises: a silicon-containing material and a carbonaceous material. The non-aqueous electrolyte comprises at least one cyclic ester selected from the group consisting of cyclic sulfates, cyclic sulfites, and sultones. The content of carbon nanotubes in the negative electrode mixture is greater than 0.005% by mass and less than 0.05% by mass. Hereinafter, the silicon-containing material is sometimes referred to as the Si-containing material, and the carbon nanotube is sometimes referred to as CNT. In addition, the above-mentioned cyclic ester is sometimes referred to as the first component.

[0020] According to this structure, in the non-aqueous electrolyte secondary battery of the present disclosure, although CNT is used, as mentioned above, the reduction of the non-aqueous electrolyte after repeated charge and discharge can be suppressed. The details of the reasons why the reduction of the non-aqueous electrolyte is suppressed are not clear, but it is believed that the reason is that, when the negative electrode mixture does not contain CNT, even if the first component is used for the non-aqueous electrolyte, the reduction suppression effect of the non-aqueous electrolyte is not seen, and therefore, the first component acts on CNT, so that the side reaction in which CNT directly or indirectly participates is suppressed. By using the first component, it is possible to obtain a sufficient reduction suppression effect of the non-aqueous electrolyte for compensating for the reduction of the non-aqueous electrolyte used with CNT.

[0021] In the non-aqueous electrolyte secondary battery disclosed herein, by using the first component, the side reaction in the negative electrode is suppressed, and therefore, the electrons are preferentially consumed by the charge and discharge reaction. Therefore, the reduction in capacity in the initial stage of charge and discharge can be suppressed. In addition, the negative electrode mixture contains CNT, so that although the Si-containing material is used as the negative electrode active material, the cutting off of the conductive path in the negative electrode mixture during repeated charge and discharge is suppressed. In addition, by the first component, the side reaction can also be suppressed during repeated charge and discharge, and therefore, the reduction in capacity after repeated charge and discharge can be suppressed. Thus, excellent cycle characteristics can be ensured.

[0022] It should be noted that when the content of CNT in the negative electrode mixture is less than 0.005% by mass, even if CNT is used in the negative electrode mixture, the reduction of the non-aqueous electrolyte is not obvious. In the negative electrode mixture containing CNT at this content, even if the non-aqueous electrolyte containing the first component is combined, the reduction inhibition effect of the non-aqueous electrolyte produced by the first component is basically not exerted. On the other hand, even in the negative electrode mixture with a content of CNT exceeding 0.05% by mass, the non-aqueous electrolyte containing the first component is combined, and the reduction inhibition effect of the non-aqueous electrolyte produced by the first component is also small. In the existing non-aqueous electrolyte secondary battery, when CNT is used in the negative electrode mixture, as shown in patent documents 1 and 2, the content of CNT in the negative electrode mixture is 0.1% by mass or more and about 9% by mass. In this existing non-aqueous electrolyte secondary battery, even if a non-aqueous electrolyte containing the first component is used, the consumption of the non-aqueous electrolyte produced by using CNT is obvious, and the reduction inhibition effect of the non-aqueous electrolyte produced by the first component is basically not obtained, or the case obtained is also small.

[0023] Hereinafter, the nonaqueous electrolyte secondary battery of the present disclosure will be specifically described with respect to each component.

[0024] (negative electrode)

[0025] The negative electrode has a negative electrode mixture. The negative electrode may have a negative electrode mixture and a negative electrode current collector that holds the negative electrode mixture. The negative electrode usually has a layered negative electrode mixture (hereinafter referred to as a negative electrode mixture layer). The negative electrode mixture contains a negative electrode active material and CNTs. The negative electrode mixture may further contain at least one selected from the group consisting of a binder, a thickener, and a conductive agent other than CNTs.

[0026] (Negative electrode active material)

[0027] As the negative electrode active material, a material that can electrochemically absorb and release lithium ions is used. The negative electrode active material includes: a Si-containing material and a carbonaceous material. Compared with the Si-containing material, the carbonaceous material has a smaller degree of expansion and contraction during charge and discharge. By using the Si-containing material and the carbonaceous material together, the contact state between the negative electrode active material particles and between the negative electrode mixture and the negative electrode collector can be better maintained during repeated charge and discharge. Thus, by combining the carbonaceous material with the Si-containing material, it is easy to ensure the high capacity of the Si-containing material and to ensure high cycle characteristics. The negative electrode active material may contain other negative electrode active materials other than the Si-containing material and the carbonaceous material as needed. As other negative electrode active materials, for example, at least one selected from the group consisting of Sn compounds such as Sn single substance, Sn alloy, and Sn oxide can be cited.

[0028] (Materials containing Si)

[0029] Examples of the Si-containing material include elemental Si, silicon alloys, silicon compounds (such as silicon oxides), and composite materials in which silicon particles (fine Si phases) are dispersed in a lithium ion conducting phase (matrix). Examples of the silicon oxide include SiO x . For x, for example, 0.5 ≤ x < 2, and it can be 0.8 ≤ x ≤ 1.6.

[0030] From the viewpoint of ensuring higher cycle characteristics, the Si-containing material preferably includes the above composite materials. The lithium ion conducting phase preferably includes at least one selected from the group consisting of SiO2 phase and silicate phase. The lithium ion conducting phase may further include a carbon phase. The lithium ion conducting phase can form an amorphous phase. The Si-containing material may include composite materials in which silicon particles are dispersed in the SiO2 phase, composite materials in which silicon particles are dispersed in the silicate phase, composite materials in which silicon particles are dispersed in the carbon phase, and the like.

[0031] The SiO2 phase is an amorphous phase containing 95% by mass or more of silicon dioxide. The composite material obtained by dispersing silicon particles in the SiO2 phase is represented by SiO x , and for x, for example, it can be in the above range. SiO x For example, it can be obtained as follows: heat-treat silicon monoxide, and separate it into a SiO2 phase and fine Si phases by disproportionation reaction, whereby it can be obtained. When observing the particle cross-section of SiO x using a transmission electron microscope (TEM: Transmission Electron Microscope), silicon particles dispersed in the SiO2 phase can be confirmed.

[0032] The silicate phase preferably includes at least one of an alkali metal element (Group 1 element other than hydrogen in the long-period periodic table) and a Group 2 element in the long-period periodic table. The alkali metal elements include lithium (Li), potassium (K), sodium (Na), etc. The Group 2 elements include magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), etc. The lithium silicate phase may have a composition represented by the formula: Li 2y SiO 2+y (0 < y < 2). y can be 1 / 2 or 1. The composite material obtained by dispersing silicon particles in the silicate phase can be obtained, for example, as follows: stir and pulverize a mixture of a silicate and raw silicon in a ball mill or the like, make it into fine particles, and then heat-treat the mixture in an inert atmosphere.

[0033] The content of the silicon particles dispersed in the silicate phase can be 30% by mass or more and 95% by mass or less, and can be 35% by mass or more and 75% by mass or less, relative to the whole composite material.

[0034] The carbon phase includes, for example, amorphous carbon with low crystallinity. Amorphous carbon can be, for example, easily graphitized carbon (hard carbon) or difficultly graphitized carbon (soft carbon). A composite material obtained by dispersing silicon particles in the carbon phase can be obtained, for example, as follows: a mixture of a carbon source and raw silicon is pulverized while stirring in a ball mill, etc., and after fine particles are formed, the mixture is heat-treated in an inert atmosphere, thereby obtaining. Sugars such as carboxymethyl cellulose (CMC) and water-soluble resins such as polyvinyl pyrrolidone are used as carbon sources.

[0035] The composition of the Si-containing material can be obtained, for example, by obtaining a reflected electron image of the cross section of the negative electrode mixture layer using a field emission scanning electron microscope (FE-SEM), observing the particles of the Si-containing material, and performing elemental analysis on the observed particles of the Si-containing material. The elemental analysis is performed using, for example, an electron probe microanalyzer (EPMA) analysis. Based on the above analysis, the composition of the lithium ion conductive phase can also be obtained.

[0036] The Si-containing material may be used alone or in combination of two or more.

[0037] The Si-containing material is, for example, a granular material. The average particle size (D50) of the Si-containing material is, for example, 1 μm or more and 25 μm or less, preferably 4 μm or more and 15 μm or less. Within the above range, good battery performance is easily obtained.

[0038] In this specification, the average particle size (D50) refers to the particle size (volume average particle size) at which the volume cumulative value is 50% in the particle size distribution measured by laser diffraction scattering. For example, the measuring device that can be used is "LA-750" manufactured by HORIBA.

[0039] From the viewpoint of improving conductivity, at least a portion of the surface of the Si-containing material particles may be covered with a conductive layer. The conductive layer comprises a conductive material such as conductive carbon. The amount of the conductive layer covered is, for example, 1 part by mass or more and 10 parts by mass or less per 100 parts by mass of the Si-containing material particles and the conductive layer. The Si-containing material particles having a conductive layer on the surface can be obtained, for example, by mixing coal pitch and the like with the Si-containing material particles and heat treating them in an inactive atmosphere.

[0040] The volume change of Si-containing materials due to expansion and contraction during charging and discharging is large. Therefore, if the ratio of Si-containing materials in the negative electrode active material increases, the cycle characteristics are likely to decrease. According to the present disclosure, the negative electrode mixture contains a specific content of CNT. Therefore, when the ratio of Si-containing materials in the negative electrode active material is large, the cutting of the conductive path is also suppressed, and high cycle characteristics are easily ensured. The ratio of Si-containing materials in the negative electrode active material is preferably 4% by mass or more, and can be 5% by mass or more. The ratio of Si-containing materials is preferably 15% by mass or less, and can be 10% by mass or less. These lower limits and upper limits can be arbitrarily combined.

[0041] (Carbon material)

[0042] Examples of the carbonaceous material include graphite, easily graphitizable carbon (soft carbon), and hardly graphitizable carbon (hard carbon). The carbonaceous material may be used alone or in combination of two or more.

[0043] From the aspects of excellent charge and discharge stability and small irreversible capacity, graphite is preferred as the carbonaceous material. As graphite, for example, natural graphite, artificial graphite, and graphitized mesophase carbon particles can be cited. The graphite particles may partially contain amorphous carbon, easily graphitized carbon, and difficultly graphitized carbon.

[0044] Graphite refers to: a carbonaceous material with a developed graphite-type crystal structure. The interplanar spacing d002 of the (002) plane of graphite measured by X-ray diffraction method can be, for example, less than 0.340 nm, or can be greater than 0.3354 nm and less than 0.340 nm. In addition, the crystallite size Lc(002) of graphite can be, for example, greater than 5 nm, or can be greater than 5 nm and less than 200 nm. The crystallite size Lc(002) is measured, for example, according to the Scherrer method. When the interplanar spacing d002 of the (002) plane of graphite and the crystallite size Lc(002) are within the above range, high capacity is easily obtained.

[0045] The ratio of the carbonaceous material in the negative electrode active material is, for example, 97% by mass or less, 96% by mass or less, or 95% by mass or less. The ratio of the carbonaceous material in the negative electrode active material is, for example, 76% by mass or more, 80% by mass or more, 85% by mass or more, or 90% by mass or more. These lower limits and upper limits may be arbitrarily combined.

[0046] In the negative electrode active material, the ratio of the total amount of Si-containing material and carbonaceous material is preferably 90% by mass or more, and can be 95% by mass or more or 98% by mass or more. In the negative electrode active material, the ratio of the total amount of Si-containing material and carbonaceous material is 100% by mass or less. The negative electrode active material can be composed only of Si-containing material and carbonaceous material.

[0047] (CNT)

[0048] CNT is a carbonaceous material with a nanometer diameter and a structure in which a sheet (graphene) of a six-membered ring network formed by carbon atoms is rolled into a cylindrical shape. CNT has excellent electrical conductivity. When the number of layers of graphene constituting the cylindrical structure is one, it is called a single-walled carbon nanotube (SWCNT). When the number of layers is multiple, it is called a multi-walled carbon nanotube (MWCNT).

[0049] The CNT preferably includes SWCNT. In this case, in addition to being easy to ensure higher cycle characteristics, it is easy to further demonstrate the effect of suppressing the reduction of the non-aqueous electrolyte by the first component.

[0050] The ratio of SWCNT to CNT is, for example, 50% or more, 75% or more, or 90% or more. The ratio of SWCNT to CNT is 100% or less.

[0051] It should be noted that the ratio of SWCNTs in CNTs refers to the ratio of the number of SWCNTs to the number of CNTs as a whole.

[0052] The inclusion of CNTs in the negative electrode mixture can be confirmed from, for example, a scanning electron microscope (SEM) image of a cross section of the negative electrode mixture layer.

[0053] The ratio of SWCNTs to CNTs contained in the negative electrode mixture was determined by the following method.

[0054] Using SEM, a cross section of the negative electrode mixture layer or an image of CNTs is obtained. In the SEM image, a plurality of CNTs (e.g., 50 to 200) are randomly selected and observed to determine the number of SWCNTs and the ratio of the number of SWCNTs to the total number of selected CNTs is calculated.

[0055] The content of CNT in the negative electrode mixture is 0.005 mass % or more, can be 0.01 mass % or more or 0.015 mass % or more, can be 0.02 mass % or more. When the content of CNT is in this range, higher cycle characteristics can be ensured, and the reduction inhibition effect of the nonaqueous electrolyte produced by the nonaqueous electrolyte comprising the first component is easy to be more obvious. The content of CNT is 0.05 mass % or less, can be 0.03 mass % or less. When the content of CNT is in this range, by using the nonaqueous electrolyte comprising the first component, the reduction of the nonaqueous electrolyte can be further suppressed. These lower limits and upper limits can be arbitrarily combined.

[0056] Quantitative analysis of CNTs can be performed by combining Raman spectroscopy and thermogravimetric analysis, for example.

[0057] From the viewpoint of reducing the cutoff of the conductive path during charge and discharge, the average diameter of the CNT is, for example, 1 nm to 10 nm, or 1 nm to 5 nm.

[0058] From the viewpoint of reducing the disconnection of the conductive path during charge and discharge, the average length of the CNT is, for example, 1 μm to 100 μm, or 5 μm to 20 μm.

[0059] The average length and average diameter of CNT can be obtained from the cross section of the negative electrode mixture layer or the image of CNT by using at least one of SEM and TEM. More specifically, a plurality of CNTs (e.g., 50 to 200) are randomly selected from the captured image, and the length and diameter are measured and averaged to obtain the average length and average diameter. It should be noted that the length of CNT refers to the length of CNT when it is stretched in a straight line.

[0060] (other)

[0061] As a binder, for example, a resin material is used. As a binder, for example, fluororesins (for example, polytetrafluoroethylene, polyvinylidene fluoride), polyolefin resins (for example, polyethylene, polypropylene), polyamide resins (for example, aromatic polyamide resins), polyimide resins (for example, polyimide, polyamide-imide), acrylic resins (for example, polyacrylic acid, polymethacrylic acid, acrylic acid-methacrylic acid copolymers, ethylene-acrylic acid copolymers, or their salts), vinyl resins (for example, polyvinyl acetate), rubber-like materials (for example, styrene-butadiene copolymer rubber (SBR)). The binder can be used alone or in combination of two or more.

[0062] As the thickener, for example, cellulose derivatives such as cellulose ether can be cited. As the cellulose derivative, CMC and its modified bodies, methyl cellulose, etc. can be cited. The modified bodies of CMC also include salts of CMC. As the salt, alkali metal salts (such as sodium salts), ammonium salts, etc. can be cited. The thickener can be used alone or in combination of two or more.

[0063] As the conductive agent other than CNT, for example, conductive fibers other than CNT and conductive particles can be cited. As the conductive fiber, carbon fiber, metal fiber, etc. can be cited. As the conductive particles, conductive carbon (carbon black, etc.), metal powder, etc. can be cited. The conductive agent can be used alone or in combination of two or more.

[0064] The negative electrode current collector can be selected according to the type of the nonaqueous electrolyte secondary battery. As the negative electrode current collector, for example, those in sheet form can be cited. As the current collector, metal foil or the like can also be used. In addition, as the current collector, those that are porous can also be used. As the porous current collector, for example, those in mesh form, punching sheets, and porous metal mesh can be cited.

[0065] Examples of the material of the negative electrode current collector include stainless steel, nickel, nickel alloys, copper, and copper alloys.

[0066] The thickness of the negative electrode current collector is not particularly limited, and may be, for example, 1 to 50 μm, or 5 to 30 μm.

[0067] The negative electrode can be formed, for example, by applying a negative electrode slurry in which the constituent components of the negative electrode mixture are dispersed in a dispersion medium to the surface of the negative electrode collector and drying it. The dried coating can be rolled as needed. The negative electrode mixture layer can be formed on one surface of a sheet-like negative electrode collector or on both surfaces.

[0068] The dispersion medium is not particularly limited, and examples thereof include water, alcohols (eg, ethanol), ethers (eg, tetrahydrofuran), amides (eg, dimethylformamide), N-methyl-2-pyrrolidone (NMP), or mixed solvents thereof.

[0069] (positive electrode)

[0070] The positive electrode may include: a positive electrode current collector, and a positive electrode mixture layer supported on the surface of the positive electrode current collector. The positive electrode mixture layer may be formed as follows: a positive electrode slurry in which a positive electrode mixture is dispersed in a dispersion medium is applied to the surface of the positive electrode current collector and dried, thereby forming the positive electrode current collector. The dried coating may be rolled as required. The positive electrode mixture layer may be formed on one surface of the positive electrode current collector or on both surfaces. The positive electrode mixture contains a positive electrode active material as an essential component, and may contain a binder, a conductive agent, etc. as arbitrary components. As a dispersion medium, for example, it may be selected from those exemplified for the negative electrode.

[0071] As the positive electrode active material, a composite oxide containing lithium and a transition metal is used, for example. As the transition metal, Ni, Co, Mn, etc. can be cited, for example. As the composite oxide containing lithium and a transition metal, Li a CoO2, Li a NiO2, Li a MnO2, Li a Co b1 Ni 1-b1 O2, Li a Co b1 M 1-b1 O c1 、Li a Ni 1-b1 M b1 O c1 、Li a Mn2O4, Li a Mn 2-b1 M b1 O4. Here, a = 0 to 1.2, b1 = 0 to 0.9, c1 = 2.0 to 2.3. M is at least one selected from the group consisting of Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb, and B. It should be noted that the value of a representing the molar ratio of lithium increases or decreases according to charge and discharge.

[0072] Among them, Li a Ni b2 M 1-b2 O2 (0 < a ≤ 1.2, 0.3 ≤ b2 ≤ 1, M is at least one selected from the group consisting of Mn, Co, and Al) is shown as the lithium nickel composite oxide. From the viewpoint of high capacity, it is more preferably satisfied that 0.85 ≤ b2 ≤ 1. From the viewpoint of the stability of the crystal structure, Li a Ni b2 Co c2 Al d O2 (0 < a ≤ 1.2, 0.85 ≤ b2 < 1, 0 < c2 ≤ 0.15, 0 < d ≤ 0.1, b2 + c2 + d = 1) is further preferred.

[0073] As the binder, the resin materials exemplified in the negative electrode can be used, etc. As the conductive agent, it can be selected from those exemplified in the negative electrode, for example. As the conductive agent, graphite can also be used.

[0074] The shape and thickness of the positive electrode current collector can be selected from the shapes and ranges described for the negative electrode current collector, respectively. As the material of the positive electrode current collector, stainless steel, aluminum, aluminum alloy, titanium, etc. can be cited, for example.

[0075] (Non-aqueous electrolyte)

[0076] As the non-aqueous electrolyte, a liquid non-aqueous electrolyte is generally used. The non-aqueous electrolyte generally contains a non-aqueous solvent and a lithium salt dissolved in the non-aqueous solvent, and in addition to these, further contains a first component.

[0077] (1st ingredient)

[0078] As the first component, at least one selected from the group consisting of cyclic sulfate, cyclic sulfite, and sultone is used. The first component may contain at least a ring-constituting unit such as -S(=O)2-O- or -S(=O)-O-.

[0079] Examples of the cyclic sulfate ester include alkylene sulfate and alkenylene sulfate. 2-4 Alkylene esters, sulfuric acid C 2-4 Alkenylene esters, etc. Specific examples of the cyclic sulfate ester include ethylene sulfate, propylene sulfate, trimethylene sulfate, butylene sulfate, and vinylene sulfate.

[0080] Examples of the cyclic sulfite include alkylene sulfites and alkenylene sulfites. 2-4 Alkylene esters, sulfite C 2-4 Alkenylene esters, etc. Specific examples of the cyclic sulfite include ethylene sulfite, propylene sulfite, trimethylene sulfite, butylene sulfite, and vinylene sulfite.

[0081] As sultone, alkane sultone, olefin sultone, etc. can be mentioned. As sultone, C 3-5 Alkane sultone, C 3-5 Olefin sultones, etc. Specific examples of sultones include 1,3-propane sultone, 1,4-butane sultone, and 1,3-propene sultone.

[0082] The first component also includes one or more substituents. In the first component, the carbon atom constituting the ring of the first component may have a substituent. As the substituent, an alkyl group, a hydroxyalkyl group, a hydroxyl group, an alkoxy group, a halogen atom, etc. may be mentioned. The carbon number of the substituent may be 1 to 4 or 1 to 3. As the halogen atom, a chlorine atom, a fluorine atom, etc. may be mentioned.

[0083] As the first component, sulfuric acid C is preferred. 2-4 Alkylene esters, sulfite C 2-4 Alkylene esters, C 3-5 Alkane sultone, C 3-5 Olefin sultones.

[0084] The nonaqueous electrolyte may include one first component or a combination of two or more first components.

[0085] The content of the first component in the non-aqueous electrolyte is, for example, less than 5% by mass, and may be less than 3% by mass. When the content of the first component is in this range, the reduction of the non-aqueous electrolyte can be further suppressed. From the viewpoint of further improving the reduction suppression effect of the non-aqueous electrolyte, it is preferred that the content of the first component in the non-aqueous electrolyte be set to less than 2% by mass. It is believed that in this case, the viscosity of the non-aqueous electrolyte can be suppressed relatively low, and the charge and discharge reaction can be carried out more uniformly, so the consumption of the non-aqueous electrolyte is suppressed as a whole. In the non-aqueous electrolyte secondary battery, the content of the first component in the non-aqueous electrolyte changes during storage or charge and discharge. Therefore, in the non-aqueous electrolyte in the non-aqueous electrolyte secondary battery, the first component remains as long as it is at a concentration above the detection limit. The content of the first component in the non-aqueous electrolyte can be more than 0.01% by mass.

[0086] It should be noted that the content of the first component in the nonaqueous electrolyte used in the manufacture of the nonaqueous electrolyte secondary battery can be more than 0.1 mass %, can be more than 0.3 mass % or more than 0.5 mass %. The content of the first component in the nonaqueous electrolyte used in the manufacture of the nonaqueous electrolyte secondary battery is, for example, less than 5 mass %, can be less than 3 mass % or less than 2 mass %. These lower limits and upper limits can be combined arbitrarily. By using the nonaqueous electrolyte of this scope in the content of the first component for the manufacture of the battery, the reduction of the nonaqueous electrolyte after repeated charge and discharge can be effectively suppressed.

[0087] The content of the first component in the nonaqueous electrolyte can be determined, for example, using gas chromatography under the following conditions.

[0088] Measuring device: GC-2010Plus manufactured by Shimadzu Corporation

[0089] Column: HP-1 (1 μm×60 m) manufactured by J&W

[0090] Line speed: 30.0cm / sec

[0091] Inlet temperature: 270℃

[0092] Detector: FID 290℃(sens.10 1 )

[0093] (Non-aqueous solvent)

[0094] As non-aqueous solvents, for example, cyclic carbonates, chain carbonates, cyclic carboxylates, and chain carboxylates can be cited. As cyclic carbonates, propylene carbonate (PC), ethylene carbonate (EC), etc. can be cited. As chain carbonates, diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), etc. can be cited. As cyclic carboxylates, γ-butyrolactone (GBL), γ-valerolactone (GVL), etc. can be cited. As chain carboxylates, methyl formate, ethyl formate, propyl formate, methyl acetate (MA), ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, etc. can be cited. The non-aqueous electrolyte can contain one non-aqueous solvent, or it can contain a combination of two or more non-aqueous solvents. When the non-aqueous electrolyte contains a chain carboxylate, it is easy to cause side reactions when combined with a negative electrode mixture containing CNT. However, in this case, the effect produced by using the first component is also significantly obtained. This suppresses side reactions and ensures high cycle characteristics. When the non-aqueous electrolyte contains at least MA as the chain carboxylic acid ester, this effect becomes significant, which is more preferred.

[0095] (Lithium Salt)

[0096] Examples of lithium salts include LiClO4, LiBF4, LiPF6, LiAlCl4, LiSbF6, LiSCN, LiCF3SO3, LiCF3CO2, LiAsF6, LiB 10 Cl 10 , lithium of lower aliphatic carboxylate, LiCl, LiBr, LiI, borate, imide salt. Examples of borate include lithium bis(1,2-benzenediol (2-)-O,O')borate, lithium bis(2,3-naphthalenediol (2-)-O,O')borate, lithium bis(2,2'-biphenylediol (2-)-O,O')borate, and lithium bis(5-fluoro-2-ol-1-benzenesulfonic acid-O,O')borate. Examples of imide salt include lithium bis(fluorosulfonyl imide) (LiN(FSO2)2), lithium bis(trifluoromethanesulfonic acid imide) (LiN(CF3SO2)2), lithium trifluoromethanesulfonic acid nonafluorobutanesulfonic acid imide (LiN(CF3SO2)(C4F9SO2)), and lithium bis(pentafluoroethanesulfonic acid imide) (LiN(C2F5SO2)2). The nonaqueous electrolyte may contain one lithium salt or a combination of two or more lithium salts.

[0097] The concentration of the lithium salt in the non-aqueous electrolyte is, for example, 0.5 mol / L or more and 2 mol / L or less.

[0098] The non-aqueous electrolyte may contain other additives. The other additives are referred to as the second component. As the second component, for example, at least one selected from the group consisting of vinylene carbonate, fluoroethylene carbonate, and vinylethylene carbonate can be cited.

[0099] (Separator)

[0100] It is usually desirable to sandwich the separator between the positive electrode and the negative electrode. The separator has a high ion permeability and has moderate mechanical strength and insulation. As the separator, for example, a microporous film, a woven fabric, or a non-woven fabric, or a laminate of at least two of them can be used. As the material of the separator, polyolefins (such as polypropylene, polyethylene) are preferred.

[0101] (other)

[0102] As an example of the structure of a non-aqueous electrolyte secondary battery, an electrode group in which a positive electrode and a negative electrode are wound across a separator and a structure in which a non-aqueous electrolyte is contained in an outer shell can be cited. Alternatively, an electrode group in other forms such as a stacked electrode group in which a positive electrode and a negative electrode are stacked across a separator can also be used instead of a wound electrode group. The non-aqueous electrolyte secondary battery can be, for example, in any form such as a cylindrical type, a square type, a coin type, a button type, and a laminated type.

[0103] Below, refer to Figure 1 The structure of a square nonaqueous electrolyte secondary battery as an example of the nonaqueous electrolyte secondary battery disclosed in the present invention will be described. Figure 1 This is a schematic perspective view with a portion of the nonaqueous electrolyte secondary battery according to one embodiment of the present disclosure cut away.

[0104] The battery comprises: a square battery case 4 with a bottom, an electrode group 1 housed in the battery case 4, and a non-aqueous electrolyte. The electrode group 1 comprises: a long strip-shaped negative electrode, a long strip-shaped positive electrode, and a separator sandwiched between them to prevent direct contact. The electrode group 1 can be formed by winding the negative electrode, the positive electrode, and the separator around a flat winding core as the center and removing the winding core.

[0105] One end of the negative lead 3 is mounted on the negative electrode collector of the negative electrode by welding or the like. The other end of the negative lead 3 is electrically connected to the negative terminal 6 provided on the sealing plate 5 via a resin insulating plate. The negative terminal 6 is insulated from the sealing plate 5 by a resin gasket 7. One end of the positive lead 2 is mounted on the positive electrode collector of the positive electrode by welding or the like. The other end of the positive lead 2 is connected to the back of the sealing plate 5 via an insulating plate. That is, the positive lead 2 is electrically connected to the battery case 4 which also serves as the positive terminal. The insulating plate isolates the electrode group 1 from the sealing plate 5 and isolates the negative lead 3 from the battery case 4. The periphery of the sealing plate 5 is fitted into the opening end of the battery case 4, and the fitting portion is laser welded. In this way, the opening of the battery case 4 is sealed by the sealing plate 5. The injection hole for the electrolyte provided in the sealing plate 5 is blocked by the sealing plug 8.

[0106] [Example]

[0107] Hereinafter, the present disclosure will be specifically described based on Examples and Comparative Examples, but the present invention is not limited to the following Examples.

[0108] 《Examples 1 to 6 and Comparative Examples 1 to 9》

[0109] A nonaqueous electrolyte secondary battery was produced and evaluated according to the following procedure.

[0110] (1) Preparation of negative electrode

[0111] An appropriate amount of water is added to the negative electrode mixture and mixed to obtain a negative electrode slurry. The negative electrode mixture contains a mixture of a negative electrode active material, a binder, and a conductive agent.

[0112] A mixture of a Si-containing material and graphite (average particle size (D50) 25 μm) was used as the negative electrode active material. The Si-containing material used was Li-ion, the surface of which was covered with a conductive layer containing conductive carbon. 2y SiO 2+y Particles (y=1, average particle size (D50) 10 μm) and SiO2 with a conductive layer containing conductive carbon on the surface x Particles (x=1, average particle size (D50) 5 μm). Li except for the conductive layer 2y SiO 2+y Particles and SiO2 except the conductive layer x The mass ratio of the particles was set to 1:1. In the negative electrode active material, the mass ratio of the Si-containing material excluding the conductive layer to the graphite was set to 6:94.

[0113] Sodium polyacrylate (PAA-Na), sodium salt of CMC (CMC-Na) and SBR were used as the binder, and CNT (average diameter of about 1.6 nm, average length of about 5 μm) containing 90 mass % or more of SWCNT was used as the conductive agent.

[0114] The content of CNT in the negative electrode mixture was set to the value shown in Table 1. The content of PAA-Na, CMC-Na, and SBR in the negative electrode mixture was each set to 1% by mass.

[0115] Next, the negative electrode slurry was applied to the surface of the copper foil, and after the coating was dried, it was rolled to form a negative electrode mixture layer (thickness 80 μm, density 1.6 g / cm 3 ), and obtain the negative electrode.

[0116] (2) Preparation of positive electrode

[0117] In lithium-containing composite oxides (LiNi 0.8 Co 0.18 Al 0.02O2) 95 mass parts, add 2.5 mass parts of acetylene black, 2.5 mass parts of polyvinylidene fluoride and an appropriate amount of NMP, and mix to obtain a positive electrode slurry. Next, the positive electrode slurry is applied to the surface of the aluminum foil, and after the coating is dried, it is rolled to form a positive electrode mixture layer (thickness 95μm, density 3.6g / cm 3 ) to obtain the positive electrode.

[0118] (3) Preparation of non-aqueous electrolyte

[0119] LiPF6 and the first component shown in Table 1 as needed are dissolved in a mixed solvent of EC, DMC and MA (EC: DMC: MA = 20: 60: 20 (volume ratio)) to prepare a non-aqueous electrolyte. The concentration of LiPF6 in the non-aqueous electrolyte is set to 1.35 mol / L. The concentration (initial concentration) of the first component in the prepared non-aqueous electrolyte is set to the value (mass %) shown as the amount of the first component added in Table 1.

[0120] (4) Fabrication of non-aqueous electrolyte secondary batteries

[0121] A positive electrode lead made of Al is installed on the positive electrode obtained in the above, and a negative electrode lead made of Ni is installed on the negative electrode obtained in the above. In an inert gas atmosphere, the positive electrode and the negative electrode are wound into a spiral shape with a polyethylene film (separator) between them to produce a wound electrode group. The electrode group is housed in a bag-shaped outer shell formed by a laminate having an Al layer, and after a specified amount of the above-mentioned non-aqueous electrolyte is injected, the outer shell is sealed to produce a non-aqueous electrolyte secondary battery. It should be noted that when the electrode group is housed in the outer shell, a portion of the positive electrode lead and the negative electrode lead are exposed to the outside from the outer shell, respectively.

[0122] (evaluate)

[0123] The nonaqueous electrolyte secondary battery was charged and discharged by the following procedure, and the remaining amount of the nonaqueous electrolyte and the capacity retention rate after the cycle were determined.

[0124] Under 45°C environment, constant current charging is performed at a current of 0.5C (180mA) until the voltage of the non-aqueous electrolyte secondary battery reaches 4.2V, and then constant voltage charging is performed at a voltage of 4.2V until the current becomes 0.05C (18mA). After pausing for 10 minutes, constant current discharge is performed at a current of 0.7C (252mA) until the voltage of the non-aqueous electrolyte secondary battery reaches 2.5V. Calculate the discharge capacity (Ci) at this time. This cycle of charging, pausing and discharging is regarded as one cycle, repeated 400 times, and the discharge capacity (Cc) of the 400th cycle is calculated. The ratio (%) of the discharge capacity Cc when the initial discharge capacity Ci is set to 100% is calculated as the capacity retention rate.

[0125] In addition, the non-aqueous electrolyte secondary battery after 400 cycles was decomposed, the residual non-aqueous electrolyte was recovered, and the volume was calculated. The ratio (%) of the volume of the residual non-aqueous electrolyte when the initial volume of the non-aqueous electrolyte was set to 100% was calculated. This ratio is shown in Table 1 as the residual amount (%) of the non-aqueous electrolyte.

[0126] The results of the examples and comparative examples are shown in Table 1. Table 1 also shows the content (mass %) of CNT in the negative electrode mixture, the type and amount (mass %) of the first component added to the nonaqueous electrolyte. In Table 1, E1 to E6 are examples 1 to 6, and C1 to C9 are comparative examples 1 to 9.

[0127] [Table 1]

[0128]

[0129] ES: Ethylene sulfite

[0130] DTD: Ethylene Sulfate

[0131] PRS: 1,3-Propylene sultone

[0132] As shown in Table 1, when the negative electrode mixture contains CNTs, the residual amount of the non-aqueous electrolyte is reduced by 3.3% compared to the case where no CNTs are included (comparison between C1 and C2). On the other hand, when the negative electrode mixture does not contain CNTs, even if the first component is added to the non-aqueous electrolyte, the residual amount of the non-aqueous electrolyte is basically unchanged (comparison between C1 and C3 to C5). In other words, when the negative electrode mixture does not contain CNTs, the first component basically does not contribute to the suppression of the reduction of the non-aqueous electrolyte. However, in the case of the negative electrode mixture containing CNTs, when the non-aqueous electrolyte containing the first component is combined, the reduction suppression effect of the non-aqueous electrolyte generated by the first component is exerted. Specifically, compared with C2 using a non-aqueous electrolyte without the first component, in E1 to E6, the residual amount of the non-aqueous electrolyte can be ensured to be comparable to or greater than that in the case where the negative electrode mixture does not contain CNTs. In addition, in E1 to E6, compared with the case where CNTs are not used or the case where the first component is not used, a high capacity retention rate can be ensured, and excellent cycle characteristics are obtained (comparison between C1 to C5 and E1 to E6). This is considered to be because the negative electrode mixture containing CNTs suppresses disconnection of the conductive path in the negative electrode mixture during repeated charge and discharge, and the use of the first component suppresses side reactions when the negative electrode mixture contains CNTs, so that electrons are preferentially consumed in the charge and discharge reaction.

[0133] It should be noted that when the content of CNT in the negative electrode mixture is less than 0.005% by mass, the reduction in the residual amount of non-aqueous electrolyte produced by using CNT is not obvious (C8). Therefore, C8 has basically no change in the residual amount of non-aqueous electrolyte compared to C3, which is a combination of a negative electrode mixture without CNT and a non-aqueous electrolyte containing the first component. In the case of a negative electrode having a CNT content exceeding 0.05% by mass and a non-aqueous electrolyte containing the first component, the reduction in the residual amount of the non-aqueous electrolyte produced by using the first component is not so significant (comparison of E2 and C2 with C7 and C9).

[0134] Industrial Applicability

[0135] The nonaqueous electrolyte secondary battery of the present disclosure is useful as a main power source for mobile communication devices, portable electronic devices, etc. However, the use of the nonaqueous electrolyte secondary battery is not limited to these.

[0136] Description of Reference Numerals

[0137] 1 Electrode set

[0138] 2 Positive lead

[0139] 3 Negative lead

[0140] 4 Battery housing

[0141] 5 Sealing plate

[0142] 6 Negative terminal

[0143] 7 Gasket

[0144] 8 Sealing plug

Claims

1. A non-aqueous electrolyte secondary battery comprising: a positive electrode, a negative electrode and a non-aqueous electrolyte, The negative electrode comprises a negative electrode mixture, wherein the negative electrode mixture comprises: a negative electrode active material capable of electrochemically storing and releasing lithium ions, and carbon nanotubes. The negative electrode active material comprises: a silicon-containing material and a carbonaceous material, The nonaqueous electrolyte includes at least one cyclic ester selected from the group consisting of cyclic sulfate esters, cyclic sulfite esters, and sultones, The content of the carbon nanotubes in the negative electrode mixture is 0.005 mass % or more and 0.05 mass % or less.

2. The nonaqueous electrolyte secondary battery according to claim 1, wherein The silicon-containing material accounts for 4 mass % or more of the negative electrode active material.

3. The nonaqueous electrolyte secondary battery according to claim 1, wherein The cyclic ester is selected from sulfuric acid C 2-4 Alkylene esters, sulfite C 2-4 Alkylene esters, C 3-5 Alkane sultones, and C 3-5 At least one selected from the group consisting of olefin sultones.

4. The nonaqueous electrolyte secondary battery according to any one of claims 1 to 3, wherein The content of the cyclic ester in the non-aqueous electrolyte is 5 mass % or less.

5. The nonaqueous electrolyte secondary battery according to any one of claims 1 to 3, wherein The carbon nanotubes include single-walled carbon nanotubes.

6. The nonaqueous electrolyte secondary battery according to claim 5, wherein The single-layer carbon nanotube accounts for more than 90% of the carbon nanotubes.

7. The nonaqueous electrolyte secondary battery according to any one of claims 1 to 3, wherein The nonaqueous electrolyte further includes a chain carboxylic acid ester.

8. The nonaqueous electrolyte secondary battery according to claim 7, wherein The nonaqueous electrolyte contains at least methyl acetate as the chain carboxylate.

Citation Information

Patent Citations

  • Compound electrode material

    JP2014146519A

  • Method of manufacturing electrode for battery

    JP2014160590A

  • Polymer lithium ion battery cathode material, polymer lithium ion battery and electronic equipment

    CN106207122A

  • KR20190101724A